1997
DOI: 10.1021/jf9607019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Isoxazole Herbicides on Protoporphyrinogen Oxidase and Porphyrin Physiology

Abstract: The biochemical and physiological effects of 10 isoxazoles were investigated. The amount of protoporphyrin IX caused to accumulate by the compounds correlated well with their herbicidal activity. Protoporphyrinogen oxidase (Protox) was inhibited competitively in the proximity of the catalytic site. However, the Protox I 50 values of the methyl esters and acid chloride derivatives were lower than expected on the basis of their in vivo herbicidal activity. The results suggest that some tolerance mechanism, other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 39 publications
0
26
0
1
Order By: Relevance
“…Clomazone applied to susceptible plants inhibits the biosynthesis of the isoprenoids compounds precursors of the photosynthetic Behavior of Bradyrhizobium japonicum strains under different herbicide concentrations The sulfentrazone inhibits the protoporphyrinogen oxidase (protox) enzyme in susceptible plants (Dayan et al, 1997), with oxidation of tissues, causing the death of the plants. In microorganisms, the sulfentrazone mechanism of action is still unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Clomazone applied to susceptible plants inhibits the biosynthesis of the isoprenoids compounds precursors of the photosynthetic Behavior of Bradyrhizobium japonicum strains under different herbicide concentrations The sulfentrazone inhibits the protoporphyrinogen oxidase (protox) enzyme in susceptible plants (Dayan et al, 1997), with oxidation of tissues, causing the death of the plants. In microorganisms, the sulfentrazone mechanism of action is still unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Singh et al [5] synthesized the cobalt(II) complexes with somea cylhydrazones, which showed afair antifungal and antibacterial activity against anumber of fungi and bacteria. Otherwise, photoluminescence, photoabsorption and photoemission studies of hydrazone thin filmsused as hole transporting material in organic light emitting diodes (OLEDs) were reported [6].Onthe other hand, isoxazole compounds have arich history with both pharmaceutical and agricultural applications due to their apoptotic activity [7], plantgrowth regulating activity [8] and antibacterial activity [9]. In the title compound, C 12 H 11 N 3 O 3 ,the molecule is almost planar, the dihedral angle formed by the benzene and isoxazole rings is 2.03 (8) …”
Section: Discussionmentioning
confidence: 99%
“…9,10 Recently, the study of herbicidal activity and biochemistry, and also the physiological studies about N-(4-chloro-2-fluoro-5-propagyloxy) phenyl-3,4,5,6-tetrahydrophthalimide analogues have been reported. 11,12 As part of other trials we reported 13,14 molecular similarity about not only inhibition activity of N-substitutionphenyl-3,4,5,6-tetrahydrophthalimide and N-substituted-phenyl-3,4-dimethylmaleimide analogues but also CoMFA analysis. Especially, it is possible to understand the results of CoMFA, CoMSIA and HQSAR, [15][16][17] about protox inhibition activity of 1-(5-methyl-3-phenylisoxazolin-5-yl)-methoxy-2-chloro-4-fluorobenzene analogues.…”
Section: Introductionmentioning
confidence: 93%